Does attachment to parents in adolescent influence internet addiction? - Buntaran, Firman Alamsyah Ario; Nor Ba’yah Abdul Kadir; Siti Marziah Zakaria (JURNAL SPIRITS, 2025)
Digital technology has had a significant impact on adolescent behavior, including the increasing prevalence of internet addiction. This study aimed to examine the influence of adolescents’ attachment to their mothers and fathers on the level of internet addiction. Parental attachment is a crucial aspect of adolescent psychosocial development that can affect patterns of internet use. A quantitative survey method was employed, involving X adolescent respondents aged 14 to 18 years, selected using purposive sampling. The instruments used in this study were the Inventory of Parent and Peer Attachment (IPPA) and the Internet Addiction Test (IAT). Based on the results of the analysis, this study concludes that parental attachment has a statistically significant relationship but does not have a practically significant effect on internet addiction in adolescents. These findings suggest that internet addiction in adolescents is influenced by various complex factors beyond the dynamics of family relationships, such as peer pressure and the influence of the digital environment. Therefore, it is essential for researchers and practitioners to develop more comprehensive intervention approaches that incorporate broader social environments and relevant psychological factors to support adolescents in managing healthy internet use.